A platinum-cobalt alloy catalyst, preparation method and application thereof
By using polyaniline modified nitrogen-doped carbon material as a support in the fuel cell catalyst and loading the platinum-cobalt alloy, the problems of high cost and poor durability of the existing catalyst are solved, and a catalyst with high activity, low platinum load and good stability are achieved.
Patent Information
- Application Number
- CN202210798467.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-07-06
AI Technical Summary
Due to the dependence of existing fuel cell cathode oxygen reduction catalysts on platinum, they are expensive and the electrochemical surface area of platinum is rapidly lost over time, affecting the durability of the catalyst.
A nitrogen-doped carbon material modified by polyaniline is used as a support, and a carbon-nitrogen shell is coated on the surface of the carbon black by thermally decomposing polyaniline, and a platinum-cobalt alloy is supported thereon to form a platinum-cobalt alloy catalyst.
The activity and stability of the catalyst are improved, the amount of platinum is used, the aggregation of metal particles is reduced, the interaction between the support and metal is enhanced, and the efficiency of oxygen reduction reaction is improved.
Smart Images

Figure CN115133050B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a platinum-cobalt alloy catalyst, a preparation method and application thereof. Background Art
[0002] The increasing depletion of fossil fuels and environmental pollution continue to drive the global demand for alternative sustainable and clean (zero byproduct emissions) energy sources. Proton exchange membrane fuel cells (PEMFCs) are considered ideal for stationary and mobile power generation due to their high energy conversion efficiency and low environmental impact. Since the slow ORR reaction at the PEMFC cathode limits its discharge performance, expensive Pt catalysts are required to promote the reaction. However, due to the corrosion of the carbon support, Pt dissolution, Ostwald ripening and aggregation, the platinum electrochemical surface area (ECSA) is lost rapidly and significantly over time, so the durability of Pt NPs is poor. In addition, the cathode oxygen reduction catalyst requires a large amount of Pt, and the cost accounts for about 30% of the entire device, which is one of the most important reasons for the high cost of fuel cells.
[0003] Combining Pt with some transition metals with 3d orbitals (e.g., Co, Ni, Fe, Cu, and Mn) has been shown to be a viable strategy for developing efficient and low-cost ORR catalysts. Previous fundamental and mechanistic studies have shown that the enhanced electrocatalytic activity of Pt-based materials may come from the 3d transition metal-induced modification of the Pt electronic structure, which suppresses the OH - The adsorption of bystander oxidizing species increases the number of active sites accessible to O2.
[0004] Carbon-based materials are considered to be good Pt nanoparticle supports due to their excellent electrical conductivity, large specific surface area, and low cost. Although carbon black is widely used as a support for Pt catalysts (specific surface area 250 m 2 g -1 ), but recent reports have shown that some undesirable properties of carbon black, such as its dense structure (smaller pore size affects the contact between Nafion ionomer and catalyst particles), corrosion of nanoparticles, and surface chemistry can reduce its electrocatalytic activity. Among them, electrochemical oxidation of the carbon surface can lead to low corrosion resistance and thus Pt dissolution / aggregation. The poor electrochemical stability of carbon supports is the main technical obstacle to the commercialization of PEMFCs.
[0005] The incorporation of nitrogen into carbon-based catalyst supports can produce a strong catalyst-support interaction, thereby significantly improving the catalytic activity and stability while reducing the Pt loading. Polyaniline (PANI) has the advantages of high conductivity, high proton conductivity, good corrosion resistance and abundant carbon and nitrogen sources. In particular, its extended π-conjugated structure ensures unique redox properties and electronic conductivity, making it a promising nitrogen-doped electrocatalytic material. Moreover, as a one-dimensional carbon nanostructured material, polyaniline-based carbon nanomaterials have better corrosion resistance than carbon materials and lower cost than non-carbon-based materials. They are also good candidate materials for loading platinum nanoparticles and are considered to be one of the effective carriers for carbon-based and non-carbon-based materials. As a catalyst carrier, PANI can provide a large specific surface area and improve the dispersion of catalyst nanoparticles on the one hand; on the other hand, it has good conductivity, which can effectively improve the efficiency of electron transfer and transmission.
[0006] Gao et al. prepared a new N-doped carbon-coated Fe3O4 ORR electrocatalyst by carbonizing the precursor of PANI-coated MIL-101-Fe. PANI, as a nitrogen source and additional carbon source, has a highly conductive skeleton in the prepared electrocatalyst, and it was demonstrated that the PANI coating contributes to its high ORR electrocatalytic activity with excellent stability in alkaline electrolyte. Ling et al. have synthesized N-doped porous carbon-supported Co-Pt bimetallic nanoalloys with extremely low Pt content via a MOF templated approach. The as-synthesized Pt-Co / NC exhibited good ORR catalytic activity in alkaline media, outperforming the benchmark 20wt% Pt / C catalyst and many previously reported high Pt-content Pt-based ORR catalysts. Wang et al. obtained an efficient noble metal-free catalyst for ORR reaction by pyrolysis of PANI and Prussian blue analog (PBA, Co3[Fe(CN)6]2). The catalyst exhibited excellent ORR performance in both alkaline and acidic electrolytes, comparable to commercial Pt / C with 20wt% Pt loading. It was demonstrated that the composite material composed of PBA and PANI will produce a highly catalytic M-NC ORR catalyst after pyrolysis and acid leaching. Therefore, the development of a catalyst with simple preparation process, low cost, high platinum utilization, good activity and stability has become a technical problem that needs to be solved urgently in this technical field. Summary of the invention
[0007] The main purpose of the present invention is to provide a fuel cell catalyst with simple preparation process, low cost, high platinum utilization rate, good activity and stability, and solve the problem that catalyst metal particles are easy to aggregate.
[0008] To achieve the above object, the present invention provides the following solutions:
[0009] A platinum-cobalt alloy catalyst comprises a carrier and an active component, wherein the carrier is a nitrogen-doped carbon material modified by polyaniline, and the active component is a platinum-cobalt alloy, and the mass percentage composition is: carrier: 70-80%, and the balance is platinum-cobalt alloy.
[0010] The platinum-cobalt alloy catalyst provided by the present invention is a platinum-cobalt alloy catalyst supported by a polyaniline-modified carbon carrier for a fuel cell, which is composed of a carrier and an active component. By structural characterization of the prepared product, it is proved that the catalyst uses a polyaniline-modified nitrogen-doped carbon material as a carrier, and the active component is a platinum-cobalt alloy, which is uniformly dispersed on the surface of the carrier, wherein the polyaniline-modified nitrogen-doped carbon material is a material modified by pyrolyzing polyaniline to modify carbon black, and electron microscopic observation shows that the surface of the carbon black is coated with a nitrogen-containing carbon shell.
[0011] Furthermore, in the platinum-cobalt alloy, the molar ratio of platinum to cobalt is 3:1 to 1:1, preferably 2:1.
[0012] Furthermore, the polyaniline-modified nitrogen-doped carbon material is a material obtained by pyrolyzing polyaniline at 600-900° C. under nitrogen protection after carbon black is coated on polyaniline. Pyrolyzing polyaniline can reduce the corrosion of the carbon carrier and successfully incorporate nitrogen into the carbon material.
[0013] A method for preparing the platinum-cobalt alloy catalyst comprises the following steps:
[0014] (1) adding carbon black to hydrochloric acid, adjusting the pH to 1, stirring evenly, adding aniline under ice bath conditions, stirring evenly to obtain a first mixed solution, dissolving ammonium persulfate in hydrochloric acid to obtain a second mixed solution, adding the second mixed solution to the first mixed solution, reacting, washing, drying, and grinding after the reaction is completed to obtain a carbon black coated polyaniline composite material (C@PANI composite material);
[0015] (2) pyrolyzing the carbon black-coated polyaniline composite material at 600-900° C. under nitrogen (N2) protection to obtain the polyaniline-modified nitrogen-doped carbon material;
[0016] (3) adding the polyaniline-modified nitrogen-doped carbon material to a mixed aqueous solution containing a soluble platinum salt and a soluble cobalt salt, ultrasonicating, drying, grinding into powder, reducing, and annealing to obtain the platinum-cobalt alloy catalyst.
[0017] Furthermore, in step (1), the mass ratio of carbon black to aniline is 1:0.5; the concentration of hydrochloric acid is 1M / L; and washing is performed with ethanol and deionized water.
[0018] Furthermore, the carbon black in step (1) is treated with H2O2 before adding hydrochloric acid. The specific steps are as follows: 5 g of carbon black is dispersed in 500 mL of H2O2, stirred at room temperature for 6 hours, filtered, washed with deionized water, and dried at 70°C for 12 hours.
[0019] Furthermore, the reaction in step (1) is carried out at 0°C for 3 hours, and the drying is freeze-drying for 12 hours.
[0020] Furthermore, the pyrolysis temperature in step (2) is 600°C, 700°C, 800°C or 900°C, preferably pyrolysis at 700°C for 2 hours.
[0021] Furthermore, in step (3), the mass volume ratio of the polyaniline-modified nitrogen-doped carbon material, the soluble platinum salt and the soluble cobalt salt is 80 mg: 2.6 mL: 0.6 mL. The soluble platinum salt is preferably H2PtCl6·6H2O, with a mass concentration of 1 g / 50 mL; the soluble cobalt salt is preferably CoCl2·6H2O, with a mass concentration of 1 g / 50 mL.
[0022] Furthermore, in step (3), the ultrasonic frequency is 10 to 30 kHz; and the reaction time is 2 to 4 hours.
[0023] Furthermore, the reduction and annealing in step (3) are both carried out under a hydrogen-argon mixed gas flow.
[0024] Furthermore, step (3) is carried out reduction and annealing in a high temperature tube furnace, wherein the reduction is first carried out at 300° C. for 2 hours and then at 600° C. for 2 hours.
[0025] The invention also discloses the application of the platinum-cobalt alloy catalyst in the field of fuel cells.
[0026] The present invention discloses the following technical effects:
[0027] The present invention combines nitrogen doping and alloying effects by coating a nitrogen-doped carbon (NC) layer on the surface of carbon black treated with H2O2, thereby strengthening the interaction between the carrier and the metal, reducing the agglomeration of metal particles, increasing the number of active sites, and improving the activity and durability of the catalyst. The present invention first synthesizes PANI on the surface of carbon powder treated with H2O2 through the π-π bond conjugation effect between carbon black and aniline. Subsequently, in a N2 atmosphere, PANI is carbonized at different temperatures to form an NC shell in situ. Compared with the uncalcined polyaniline-coated carbon black carrier, high-temperature calcination successfully incorporates N into the modified carbon carrier. The mutual transfer of electrons between the PtCo alloy and N is conducive to reducing the d-band center of Pt, thereby improving the ORR catalytic activity of PtCo / C@CN. At the same time, graphite N and pyridine N, as active sites for oxygen reduction reaction, are also conducive to improving oxygen reduction activity. While the NC shell weakens carbon corrosion, N strengthens the interaction between metal nanoparticles and the carrier, effectively preventing the aggregation of PtCo nanoparticles. To ensure the improvement of the stability of the catalyst. Obviously, the NC shell carbonized at different temperatures has different effects on the nanoparticles. By comparison, it was found that the N-doped carbon-based alloy catalyst (PtCo / C@CN-700) prepared at 700°C has a higher content of graphitic N and pyridinic N, which is conducive to promoting the oxygen reduction reaction and shows the highest oxygen reduction activity among the catalysts studied. In addition, the metal particles in the PtCo / C@CN-700 catalyst are smaller in size and less prone to aggregation, providing more active sites, giving the overall catalyst activity and stability, making it a promising candidate for the next generation of PEMFC. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 Fourier transform infrared spectrum of C@PANI prepared in Example 1 of the present invention;
[0030] Figure 2 is an X-ray photoelectron spectrum of the modified carbon support C@CN prepared in Example 1 of the present invention;
[0031] Figure 3 is a Raman spectrum of the polyaniline-modified carbon support C@CN-T prepared at different calcination temperatures in Examples 1 to 4 of the present invention;
[0032] Figure 4It is an X-ray diffraction analysis diagram of the polyaniline modified carbon-supported platinum-cobalt alloy catalyst (PtCo / C@CN) prepared in Example 1 of the present invention, the carbon-supported platinum-cobalt alloy catalyst in Comparative Example 1, and commercial platinum-carbon;
[0033] Figure 5 is a transmission electron microscopy image of the polyaniline-modified carbon-supported platinum-cobalt alloy catalyst (PtCo / C@CN) prepared in Example 1 of the present invention;
[0034] Figure 6 is a particle size distribution histogram of the polyaniline-modified carbon-supported platinum-cobalt alloy catalyst (PtCo / C@CN) prepared in Example 1 of the present invention;
[0035] Figure 7 is an oxygen reduction polarization curve of the polyaniline-modified carbon-supported platinum-cobalt alloy catalyst (PtCo / CN) prepared in Examples 1, 5 and 6 of the present invention;
[0036] Figure 8 It is a graph of oxygen reduction polarization curves of the polyaniline-modified carbon-supported platinum-cobalt alloy catalyst (PtCo / C@CN) prepared in Example 1 of the present invention, the carbon-supported platinum-cobalt alloy catalyst in Comparative Example 1, and commercial platinum-carbon. DETAILED DESCRIPTION
[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0038] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0042] The carbon black used in the examples of the present invention is commercial EC-300J carbon black.
[0043] An embodiment of the present invention provides a platinum-cobalt alloy catalyst, comprising a carrier and an active component, wherein the carrier is a nitrogen-doped carbon material modified by polyaniline, and the active component is a platinum-cobalt alloy, and the mass percentage composition is: carrier: 70-80%, and the balance is platinum-cobalt alloy.
[0044] The platinum-cobalt alloy catalyst provided in the embodiment of the present invention is a platinum-cobalt alloy catalyst supported on a polyaniline-modified carbon carrier for a fuel cell, which is composed of a carrier and an active component. By structural characterization of the prepared product, it is proved that the carrier is a nitrogen-doped carbon material modified by polyaniline, and the active component is a platinum-cobalt alloy, which is uniformly dispersed on the surface of the carrier. Among them, the nitrogen-doped carbon material modified by polyaniline is a material modified by pyrolyzing polyaniline on carbon black, and an electron microscope observes that the surface of the carbon black is covered with a nitrogen-containing carbon shell.
[0045] In the platinum-cobalt alloy, the molar ratio of platinum to cobalt is 3:1 to 1:1, preferably 2:1.
[0046] The polyaniline-modified nitrogen-doped carbon material is a material obtained by coating polyaniline with carbon black and then pyrolyzing the polyaniline at 600-900° C. under nitrogen protection.
[0047] The present invention provides a method for preparing a platinum-cobalt alloy catalyst, comprising the following steps:
[0048] (1) adding carbon black to hydrochloric acid, adjusting the pH to 1, stirring evenly, adding aniline under ice bath conditions, stirring evenly to obtain a first mixed solution, dissolving ammonium persulfate in hydrochloric acid to obtain a second mixed solution, adding the second mixed solution to the first mixed solution, reacting, washing, drying, and grinding after the reaction is completed to obtain a carbon black coated polyaniline composite material (C@PANI composite material);
[0049] (2) pyrolyzing the carbon black-coated polyaniline composite material at 600-900° C. under nitrogen N2 protection to obtain the polyaniline-modified nitrogen-doped carbon material;
[0050] (3) adding the polyaniline-modified nitrogen-doped carbon material to a mixed aqueous solution containing a soluble platinum salt and a soluble cobalt salt, ultrasonicating, drying, grinding into powder, reducing, and annealing to obtain the platinum-cobalt alloy catalyst.
[0051] The preparation method of the platinum-cobalt alloy catalyst loaded on a polyaniline-modified carbon carrier for a fuel cell of the present invention mainly comprises three steps: first, PANI is synthesized on the surface of carbon black by chemical oxidation polymerization, and a C@PANI composite material with good conductivity and large specific surface area is prepared by adjusting the pH of the reaction and the ratio of carbon black to aniline; then, the C@PANI composite material obtained above is subjected to high-temperature pyrolysis in a tubular furnace, and a carbon carrier with different nitrogen contents can be prepared by carbonizing PANI on the surface of carbon black to wrap a nitrogen-containing carbon shell and controlling the pyrolysis temperature; finally, PtCo alloy is loaded on the modified carbon carrier prepared above by an impregnation method, thereby obtaining the final platinum-cobalt alloy catalyst loaded on the polyaniline-modified carbon carrier.
[0052] In step (1), the mass ratio of carbon black to aniline is 1:0.5; the concentration of hydrochloric acid is 1M / L; and washing is performed with ethanol and deionized water.
[0053] The carbon black in step (1) is also treated with H2O2 before adding hydrochloric acid. The specific steps are as follows: 5 g of carbon black is dispersed in 500 mL of H2O2, stirred at room temperature for 6 hours, filtered, washed with deionized water, and dried at 70°C for 12 hours.
[0054] The reaction in step (1) is carried out at 0°C for 3 hours, and the drying is freeze-drying for 12 hours.
[0055] The pyrolysis temperature in step (2) is 600°C, 700°C, 800°C or 900°C, preferably pyrolysis at 700°C for 2 hours.
[0056] Step (3) The polyaniline-modified nitrogen-doped carbon material, soluble platinum salt and soluble cobalt salt are 80 mg: 2.6 mL: 0.6 mL. The soluble platinum salt is preferably H2PtCl6·6H2O, with a mass concentration of 1 g / 50 mL; the soluble cobalt salt is preferably CoCl2·6H2O, with a mass concentration of 1 g / 50 mL.
[0057] The ultrasonic frequency of step (3) is 10 to 30 kHz; and the reaction time is 2 to 4 hours.
[0058] The reduction and annealing in step (3) are both carried out under a hydrogen-argon mixed gas flow.
[0059] Step (3) is to perform reduction and annealing in a high temperature tube furnace, wherein the reduction is first performed at 300° C. for 2 hours and then at 600° C. for 2 hours.
[0060] The platinum-cobalt alloy catalyst prepared in the embodiment of the present invention is used in the field of fuel cells.
[0061] Example 1
[0062] The preparation of the platinum-cobalt alloy catalyst supported on a polyaniline-modified carbon carrier for a fuel cell comprises the following steps:
[0063] (1) Disperse 5g of carbon black in 500ml of H2O2, stir at room temperature for 6 hours, filter, wash with deionized water, and dry at 70℃ for 12 hours. Weigh 0.2g of carbon black treated with H2O2, add it to 80mL of 1M hydrochloric acid, adjust the pH to 1, and disperse it evenly by ultrasound. Under ice bath conditions, add 0.1g of aniline and stir magnetically to obtain a first mixed solution; dissolve 0.2450g of ammonium persulfate in 40mL of 1mol / L hydrochloric acid to obtain a second mixed solution, add the second mixed solution dropwise into the first mixed solution within 20 minutes, and react at 0℃ for 3h. After the reaction is completed, wash with ethanol and deionized water, freeze-dry for 12h, grind into powder for use, and obtain C@PANI composite material;
[0064] (2) placing the C@PANI composite material prepared in step (1) in a high-temperature tube furnace, heating the C@PANI composite material to 700°C at a heating rate of 8°C / min under N2 conditions, and maintaining this temperature for 2 hours, and then cooling it to room temperature to obtain the target carrier C@CN-700;
[0065] (3) Weigh 80 mg of the carrier C@CN-700 prepared in step (2), add 2.6 mL of H2PtCl6·6H2O aqueous solution (1 g / 50 mL) and 0.6 mL of CoCl2·6H2O (1 g / 50 mL) aqueous solution, mix them by ultrasonication for 3 h at a frequency of 20 kHz, dry them, grind them into powder, and reduce the powder in a tube furnace under the flow of hydrogen and argon mixed gas at 300° C. for 2 h. Then, anneal the powder at 600° C. under the flow of hydrogen and argon mixed gas for 2 h to form a polyaniline-modified nitrogen-doped carbon carrier-supported platinum-cobalt catalyst.
[0066] Example 2
[0067] The preparation of the platinum-cobalt alloy catalyst supported on a polyaniline-modified carbon carrier for a fuel cell comprises the following steps:
[0068] (1) Disperse 5g of carbon black in 500ml of H2O2, stir at room temperature for 6 hours, filter, wash with deionized water, and dry at 70℃ for 12 hours. Weigh 0.2g of carbon black treated with H2O2, add it to 80mL of 1M hydrochloric acid, adjust the pH to 1, and disperse it evenly by ultrasound. Under ice bath conditions, add 0.1g of aniline and stir magnetically to obtain a first mixed solution; dissolve 0.2450g of ammonium persulfate in 40mL of 1mol / L hydrochloric acid to obtain a second mixed solution, add the second mixed solution dropwise into the first mixed solution within 20 minutes, and react at 0℃ for 3h. After the reaction is completed, wash with ethanol and deionized water, freeze-dry for 12h, grind into powder for use, and obtain C@PANI composite material;
[0069] (2) placing the C@PANI composite material prepared in step (1) in a high-temperature tube furnace, heating the prepared C@PANI composite material to 600°C at a heating rate of 8°C / min under N2 conditions, and maintaining this temperature for 2 hours, and then cooling it to room temperature to obtain the target carrier C@CN-600;
[0070] (3) Weigh 80 mg of the carrier C@CN-600 prepared in step (2), add 2.6 mL of H2PtCl6·6H2O aqueous solution (1 g / 50 mL) and 0.6 mL of CoCl2·6H2O aqueous solution (1 g / 50 mL), mix them by ultrasonication for 3 h at a frequency of 20 kHz, dry them, grind them into powder, and reduce the powder in a tube furnace under the flow of hydrogen and argon mixed gas at 300 ° C for 2 h. Then, anneal the powder at 600 ° C under the flow of hydrogen and argon mixed gas for 2 hours to form a polyaniline-modified nitrogen-doped carbon carrier-supported platinum-cobalt catalyst.
[0071] Example 3
[0072] The preparation of the platinum-cobalt alloy catalyst supported on a polyaniline-modified carbon carrier for a fuel cell comprises the following steps:
[0073] (1) Disperse 5g of carbon black in 500ml of H2O2, stir at room temperature for 6 hours, filter, wash with deionized water, and dry at 70℃ for 12 hours. Weigh 0.2g of carbon black treated with H2O2, add it to 80mL of 1M hydrochloric acid solution, adjust the pH to 1, and disperse it evenly by ultrasound. Under ice bath conditions, add 0.1g of aniline and stir magnetically to obtain a first mixed solution. Dissolve 0.2450g of ammonium persulfate in 40mL of 1mol / L hydrochloric acid solution to obtain a second mixed solution, add the second mixed solution dropwise into the first mixed solution within 20 minutes, and react at 0℃ for 3h. After the reaction is completed, wash with ethanol and deionized water, freeze-dry for 12h, grind into powder for use, and obtain C@PANI composite material;
[0074] (2) placing the C@PANI composite material prepared in step (1) in a high-temperature tube furnace, heating the prepared C@PANI composite material to 800°C at a heating rate of 8°C / min under N2 conditions, and maintaining this temperature for 2 hours, and then cooling it to room temperature to obtain the target carrier C@CN-800;
[0075] (3) Weigh 80 mg of the carrier C@CN-800 prepared in step (2), add 2.6 mL of H2PtCl6·6H2O aqueous solution (1 g / 50 mL) and 0.6 mL of CoCl2·6H2O aqueous solution (1 g / 50 mL), mix them by ultrasonication for 3 h at a frequency of 20 kHz, dry them, grind them into powder, and reduce the powder in a tube furnace at 300 ° C for 2 h under the flow of hydrogen and argon mixed gas. Then, the powder is annealed at 600 ° C for 2 h under the flow of hydrogen and argon mixed gas to form a polyaniline-modified nitrogen-doped carbon carrier-supported platinum-cobalt catalyst.
[0076] Example 4
[0077] The preparation of the platinum-cobalt alloy catalyst supported on a polyaniline-modified carbon carrier for a fuel cell comprises the following steps:
[0078] (1) Disperse 5g of carbon black in 500ml of H2O2, stir at room temperature for 6 hours, filter, wash with deionized water, and dry at 70℃ for 12 hours. Weigh 0.2g of carbon black treated with H2O2, add it to 80mL of 1M hydrochloric acid solution, adjust the pH to 1, and disperse it evenly by ultrasound. Under ice bath conditions, add 0.1g of aniline and stir magnetically to obtain a first mixed solution; dissolve 0.2450g of ammonium persulfate in 40mL of 1mol / L hydrochloric acid solution to obtain a second mixed solution, add the second mixed solution dropwise into the first mixed solution within 20 minutes, and react at 0℃ for 3h. After the reaction is completed, wash with ethanol and deionized water, freeze-dry for 12h, grind into powder for use, and obtain C@PANI composite material;
[0079] (2) placing the C@PANI composite material prepared in step (1) in a high-temperature tube furnace, heating the prepared C@PANI composite material to 900°C at a heating rate of 8°C / min under N2 conditions, and maintaining this temperature for 2 hours, and then cooling it to room temperature to obtain the target carrier C@CN-900;
[0080] (3) Weigh 80 mg of the carrier C@CN-900 prepared in step (2), add 2.6 mL of H2PtCl6·6H2O aqueous solution (1 g / 50 mL) and 0.6 mL of CoCl2·6H2O aqueous solution (1 g / 50 mL), mix them by ultrasonication for 3 h at a frequency of 20 kHz, dry them, grind them into powder, and reduce the powder in a tube furnace at 300 ° C for 2 h under the flow of hydrogen and argon mixed gas. Then, the powder is annealed at 600 ° C for 2 h under the flow of hydrogen and argon mixed gas to form a polyaniline-modified nitrogen-doped carbon carrier-supported platinum-cobalt catalyst.
[0081] Example 5
[0082] The preparation of the platinum-cobalt alloy catalyst supported on a polyaniline-modified carbon carrier for a fuel cell comprises the following steps:
[0083] (1) Disperse 5g of carbon black in 500ml of H2O2, stir at room temperature for 6 hours, filter, wash with deionized water, and dry at 70℃ for 12 hours. Weigh 0.2g of carbon black treated with H2O2, add it to 80mL of 1M hydrochloric acid solution, adjust the pH to 1, and disperse it evenly by ultrasound. Under ice bath conditions, add 0.1g of aniline and stir magnetically to obtain a first mixed solution; dissolve 0.2450g of ammonium persulfate in 40mL of 1mol / L hydrochloric acid solution to obtain a second mixed solution, add the second mixed solution dropwise into the first mixed solution within 20 minutes, and react at 0℃ for 3h. After the reaction is completed, wash with ethanol and deionized water, freeze-dry for 12h, grind into powder for use, and obtain C@PANI composite material;
[0084] (2) placing the C@PANI composite material prepared in step (1) in a high-temperature tube furnace, heating the prepared C@PANI composite material to 700°C at a heating rate of 8°C / min under N2 conditions, and maintaining this temperature for 2 hours, and then cooling it to room temperature to obtain the target carrier C@CN-700;
[0085] (3) Weigh 80 mg of the carrier C@CN-700 prepared in step (2), add 2.7 mL of H2PtCl6·6H2O aqueous solution (1 g / 50 mL) and 0.4 mL of CoCl2·6H2O aqueous solution (1 g / 50 mL), mix them by ultrasonication for 3 h at a frequency of 20 kHz, dry them, grind them into powder, and reduce the powder in a tube furnace at 300 ° C for 2 h under the flow of hydrogen and argon mixed gas. Then, the powder is annealed at 600 ° C for 2 h under the flow of hydrogen and argon mixed gas to form a polyaniline-modified nitrogen-doped carbon carrier-supported platinum-cobalt catalyst.
[0086] Example 6
[0087] The preparation of the platinum-cobalt alloy catalyst supported on a polyaniline-modified carbon carrier for a fuel cell comprises the following steps:
[0088] (1) Disperse 5g of carbon black in 500ml of H2O2, stir at room temperature for 6 hours, filter, wash with deionized water, and dry at 70℃ for 12 hours. Weigh 0.2g of carbon black treated with H2O2, add it to 80mL of 1M hydrochloric acid solution, adjust the pH to 1, and disperse it evenly by ultrasound. Under ice bath conditions, add 0.1g of aniline and stir magnetically to obtain a first mixed solution; dissolve 0.2450g of ammonium persulfate in 40mL of 1mol / L hydrochloric acid solution to obtain a second mixed solution, add the second mixed solution dropwise into the first mixed solution within 20 minutes, and react at 0℃ for 3h. After the reaction is completed, wash with ethanol and deionized water, freeze-dry for 12h, grind into powder for use, and obtain C@PANI composite material;
[0089] (2) placing the C@PANI composite material prepared in step (1) in a high-temperature tube furnace, heating the prepared C@PANI composite material to 700°C at a heating rate of 8°C / min under N2 conditions, and maintaining this temperature for 2 hours, and then cooling it to room temperature to obtain the target carrier C@CN700;
[0090] (3) Weigh 80 mg of the carrier C@CN-700 prepared in step (2), add 2.3 mL of H2PtCl6·6H2O aqueous solution (1 g / 50 mL) and 1.0 mL of CoCl2·6H2O aqueous solution (1 g / 50 mL), mix them by ultrasonication for 3 h at a frequency of 20 kHz, dry them, grind them into powder, and reduce the powder in a tube furnace at 300 ° C for 2 h under the flow of hydrogen and argon mixed gas. Then, the powder is annealed at 600 ° C for 2 h under the flow of hydrogen and argon mixed gas to form a polyaniline-modified nitrogen-doped carbon carrier-supported platinum-cobalt catalyst.
[0091] Comparative Example 1
[0092] The preparation of the carbon black-supported platinum-cobalt alloy catalyst for fuel cells comprises the following steps:
[0093] (1) Disperse 5 g of carbon black in 500 ml of H2O2, stir at room temperature for 6 hours, filter, wash with deionized water, and dry at 70°C for 12 hours.
[0094] (2) 80 mg of carbon black treated with H2O2 was weighed and added to 2.6 mL of H2PtCl6·6H2O aqueous solution (1 g / 50 mL) and 0.6 mL of CoCl2·6H2O aqueous solution (1 g / 50 mL), respectively, and ultrasonicated for 3 h to mix them evenly, with an ultrasonic frequency of 20 kHz, dried, ground into powder, and the powder was reduced in a tube furnace at 300° C. for 2 h under the flow of hydrogen and argon mixed gas. Then, the powder was annealed at 600° C. under the flow of hydrogen and argon mixed gas for 2 h to form a carbon black-supported platinum-cobalt alloy catalyst.
[0095] Product Verification:
[0096] The products prepared in Examples 1 to 6 were structurally characterized to prove that they used carbon as a carrier, active metals were loaded on the carbon surface, the carrier was a nitrogen-doped carbon material modified by pyrolysis of polyaniline, and the active component was a platinum-cobalt alloy. Electron microscopy observation revealed that the metal nanoparticles were evenly distributed.
[0097] (1) Fourier transform infrared spectrum analysis
[0098] Figure 1 is the Fourier infrared spectrum of C@PANI prepared in Example 1 of the present invention; Figure 1 Compared with the spectrum of C, the characteristic peaks of the functional groups of C@PANI composite materials are similar to those of PANI, among which 1560cm -1 and 1475cm -1 The vibration absorption peaks are the stretching vibration peaks of C=C and C=N of PANI, 1293cm -1 and 1238cm -1 The absorption peak at 1135cm corresponds to the CN stretching vibration peak of PANI. -1 and 796cm -1 The characteristic absorption band of CH corresponding to the benzene ring proves that PANI is grown on C and also shows that the chemical structure of PANI on C has not changed fundamentally.
[0099] (2) X-ray photoelectron spectroscopy analysis
[0100] Figure 2 is the X-ray photoelectron spectrum of the modified carbon support C@CN prepared in Example 1 of the present invention. Figure 2 It can be found that there are C, N, and O peaks in the spectrum, indicating the successful doping of N.
[0101] (3) Raman spectroscopy analysis
[0102] Figure 3 is a modified carbon support prepared at different calcination temperatures in Examples 1 to 4 of the present invention, Figure 3 It can be found that each sample has a peak at about 1340 and 1600 cm-1 There are two peaks at , namely D peak (amorphous carbon) and G peak (graphite carbon). The higher the ID / IG, the more defects the carbon structure has. By comparison, it can be found that with the increase of calcination temperature, the ID / IG of the carbon carrier increases first and then decreases, and the carbon carrier prepared at 700℃ has the highest ID / IG (1.17). Therefore, C@CN-700 has the most defects in its carbon structure, which is conducive to increasing the number of nucleation sites and improving the dispersion of metal nanoparticles.
[0103] (4) X-ray diffraction analysis
[0104] Figure 4 It is the X-ray diffraction analysis diagram of the polyaniline modified carbon-supported platinum-cobalt alloy catalyst (PtCo / C@CN) prepared in Example 1 of the present invention, the platinum-cobalt alloy catalyst (PtCo / C) prepared in Comparative Example 1, and commercial (JM) Pt / C, wherein the large broad peak at 2θ=25° of PtCo / C@CN and PtCo / C corresponds to the (002) crystal plane of graphite carbon, while the peaks at 2θ=41°, 47°, 69° and 82° belong to the (111), (200), (220) and (311) crystal planes of the fcc crystal type, respectively, which are all right-shifted compared with the pure Pt peak (PDF#04-0802), and no separate Pt and Co peaks appear, indicating that Pt and Co of PtCo / C@CN and PtCo / C have formed alloy structures.
[0105] (5) Transmission electron microscopy analysis
[0106] Figure 5 This is a high-resolution transmission electron microscopy analysis image of the polyaniline-modified carbon-supported platinum-cobalt alloy catalyst (PtCo / C@CN) prepared in Example 1 of the present invention. Figure 6 The particle size distribution histogram of the polyaniline modified carbon-supported platinum-cobalt alloy catalyst (PtCo / C@CN) prepared in Example 1 of the present invention is shown in FIG. In the catalyst, the metal particles are uniformly dispersed on the carbon support, and its particle size is very small, about 2.1 nm. This is because the interaction between the nitrogen atoms on the CN shell of the support and the metal nanoparticles inhibits the agglomeration of the metal nanoparticles.
[0107] (6) Oxygen reduction polarization curve analysis
[0108] Figure 7 : is the oxygen reduction polarization curve of the polyaniline modified carbon supported platinum cobalt alloy catalyst (PtCo / C@CN) prepared in Examples 1, 5 and 6 of the present invention. Figure 7 It can be seen that when the Pt:Co molar ratio is 2:1, the half-wave potential of the catalyst is the largest, that is, the oxygen reduction activity is the highest. Figure 8The oxygen reduction polarization curves of the polyaniline modified carbon-supported platinum-cobalt alloy catalyst (PtCo / C@CN) prepared in Example 1 of the present invention, the carbon-supported platinum-cobalt alloy catalyst in Comparative Example 1, and commercial platinum-carbon are shown. By comparing the half-wave potentials of the catalysts, it is found that the half-wave potential of PtCo / C@CN is higher than that of PtCo / C, and the half-wave potential of Pt / C is higher than that of commercial Pt / C. That is, the prepared PtCo / C@CN has the highest oxygen reduction activity.
[0109] In order to investigate the stability of the prepared catalysts, accelerated stability tests (ADT) were performed on JMPt / C, PtCo / C, and PtCo / V@CN in a 0.1 M HClO4 solution saturated with N2 for 10,000 cycles at a scan rate of 100 mV s -1 , voltage range 0.6~1.0V. After ADT test, the half-wave potential of PtCo / C@CN only dropped by 6mv, which is lower than PtCo / C (10mv) and JM Pt / C (23mv). That is, the prepared PtCo / C@CN has good chemical stability.
[0110] The present invention uses polyaniline to modify carbon black, pyrolyzes polyaniline to coat the carbon black surface with a carbon nitrogen shell, and uses an impregnation method to load PtCo metal nanoparticles on the modified carbon carrier to prepare a polyaniline-modified carbon carrier-loaded platinum-cobalt catalyst. The catalyst has the advantages of low platinum loading, high catalytic activity and good chemical stability, and is conducive to promoting the further development of fuel cells.
[0111] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a platinum-cobalt alloy catalyst, characterized in that: The following steps are involved: (1) 5 g of carbon black was dispersed in 500 ml of H2O2, stirred at room temperature for 6 hours, filtered, washed with deionized water, and dried at 70°C for 12 hours. 0.2 g of carbon black treated with H2O2 was weighed and added to 80 mL of 1 M hydrochloric acid, the pH was adjusted to 1, and ultrasonic dispersion was performed to make it uniform. Under ice bath conditions, 0.1 g of aniline was added and magnetic stirring was performed to obtain a first mixed solution. 0.2450 g of ammonium persulfate was dissolved in 40 mL of 1 mol / L hydrochloric acid to obtain a second mixed solution. The second mixed solution was added dropwise into the first mixed solution within 20 minutes, and reacted at 0°C for 3 hours. After the reaction was completed, it was washed with ethanol and deionized water, freeze-dried for 12 hours, and ground into powder for use to obtain a carbon black-coated polyaniline composite material. (2) placing the carbon black-coated polyaniline composite material prepared in step (1) in a high-temperature tube furnace, heating the carbon black-coated polyaniline composite material to 700° C. at a heating rate of 8° C. / min under N2 conditions, and maintaining this temperature for 2 h, and then cooling it to room temperature to obtain a target carrier polyaniline-modified nitrogen-doped carbon material; (3) Weigh 80 mg of the nitrogen-doped carbon material modified with polyaniline prepared in step (2), add 2.6 mL of H2PtCl6·6H2O aqueous solution (1 g / 50 mL) and 0.6 mL of CoCl2·6H2O aqueous solution (1 g / 50 mL) respectively, mix them by ultrasonic treatment for 3 h at a frequency of 20 kHz, dry them, grind them into powder, reduce the powder in a tube furnace under the flow of hydrogen and argon mixed gas at 300° C. for 2 h, and then anneal the powder at 600° C. under the flow of hydrogen and argon mixed gas for 2 h to form a platinum-cobalt catalyst supported on a polyaniline-modified nitrogen-doped carbon carrier.
2. Application of the platinum-cobalt alloy catalyst prepared by the method of claim 1 in the field of fuel cells.
Citation Information
Patent Citations
Preparation method of nitrogen-doped graphene loaded platinum nano-particle catalyst
CN103372428A
Polyaniline-coated carbon carrier-containing platinum-based dealloying fuel cell catalyst, and preparation method therefor
CN106960962A